Internationalisation of higher education in Malaysia: Insights from higher education administrators - Munusamy, M.Miandy; Hashim, Azirah (AEI Insights, 2021)
The rationale for internationalisation of higher education can be political, economic, sociocultural as well as academic and incorporates motivations for assimilating an international element into higher education. Malaysia aspires to create a higher education system that ranks among the world’s leading education systems. The country has had a strong focus on internationalisation since the introduction of the National Higher Education Strategic Plan 2007-2020. Its internationalisation rationale requires that extensive initiatives and strategies are in place for the country. The study aims to evaluate the rationale for international cooperation in the Malaysian higher education internationalisation agenda. The qualitative study using expert sampling was conducted through semi-structured interviews with 15 officials in the Malaysian public higher education sector. The interview data was analysed using the qualitative data analysis software Nvivo-11. The findings indicate that the Malaysian higher education system focuses on the economic and socio-cultural rationale moderately supported by the political and academic rationale. The study also identifies that international networking through international cooperation is crucial in strengthening Malaysian higher education internationalisation. The results can assist higher education administrators and policymakers to design a comprehensive internationalisation policy to realise Malaysia’s aim to become an excellent international higher education hub and attract 250,000 international students by 2025.